Mistletoe man eaudiobook China bayles mysteries series, book 9. - Albert, Susan Wittig (China Bayles Mystery, 2005)
Best-selling author Susan Wittig Albert sets this cozy mystery in the small West Texas town of Pecan Springs. As the Christmas decorating season approaches, Thyme Seasons proprietor China Bayles feels overwhelmed. While she tries to balance her new roles of wife and step-mom with the demands of her thriving herbal shop, her business partner-and best friend-Ruby mysteriously disappears. Soon China's cantankerous mistletoe supplier Carl turns up dead. With Ruby missing and friends suspected of murder, China must investigate before tragedy strikes again.